2011
DOI: 10.1111/j.1744-7909.2011.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Optimal Defense Patterns in Nicotiana attenuata: Flowering Attenuates Herbivory-elicited Ethylene and Jasmonate SignalingF

Abstract: To defend themselves against herbivore attack, plants produce secondary metabolites, which are variously inducible and constitutively deployed, presumably to optimize their fitness benefits in light of their fitness costs. Three phytohormones, jasmonates (JA) and their active forms, the JA‐isoleucine (JA‐Ile) and ethylene (ET), are known to play central roles in the elicitation of induced defenses, but little is known about how this mediation changes over ontogeny. The Optimal Defense Theory (ODT) predicts cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 96 publications
5
74
0
1
Order By: Relevance
“…For example, the production of a phytohormone associated with direct defense in the leaves of Nicotiana attenuata have been shown to decrease as plants enter the reproductive stage [50]. In our study, plants were constrained by the amount of resources present in the soil of their pots, and reached relatively small sizes at maturity (Figure 1).…”
Section: Discussionmentioning
confidence: 74%
“…For example, the production of a phytohormone associated with direct defense in the leaves of Nicotiana attenuata have been shown to decrease as plants enter the reproductive stage [50]. In our study, plants were constrained by the amount of resources present in the soil of their pots, and reached relatively small sizes at maturity (Figure 1).…”
Section: Discussionmentioning
confidence: 74%
“…In addition to its role in defense, ET is also known to be an important regulator of developmental processes, and accordingly, ET-dependent defense patterns change during development. For instance, treating Nicotiana attenuata leaves of various ages with saliva from the Manduca sexta caterpillar showed that induced ET emission decreased with leaf and plant age (Diezel et al, 2011).…”
Section: Attacker-induced Et Signalingmentioning
confidence: 99%
“…Herbivore-induced jasmonate and ethylene signaling are influenced by plant development (Diezel et al, 2011a). To test whether plant development specifically influences M. sexta-induced IAA levels, we induced plants by simulated M. sexta attack and measured IAA levels in the leaves of early rosette, elongated, and flowering plants.…”
Section: Iaa Induction In Leaves Is Conserved Across Different Develomentioning
confidence: 99%